Contemporary developments in the Portuguese Eurasian community of the Portuguese settlement, Malacca / Chin Poh Choo - Chin , Poh Choo (1983)
This study is about the Portuguese Eurasian community of the Portuguese settlement, Malacca. The main purpose of this study is to give a clearer insight into the lives of the Portuguese Eurasians today – ie. to look into the developments that have taken place in this community. Chapter I deals with the aim or purpose of study, methodology and the problems that were faced and the steps that were taken. Chapter II gives a brief history of the Portuguese Eurasians in Malacca and it also traces the developments of this community right up to today. The social and cultural heritage of the Portuguese Eurasians are discussed in chapter III. In discussing the social and cultural heritage of the Portuguese Eurasians be used as a basic of identity today is dealt with. Chapter IV covers the intra-and inter-communal relationships. In the intra-communal relationships, emphasis is given to the solidarity that is prevalent in this community. The relationship of the Portuguese Eurasians in this settlement with other Portuguese Eurasians in Malacca is also discussed under this section. On the other hand, the relationship discussion of the inter-communal relationships is directed to the question of to what extent is this community open to charge. Chapter V deals with some of the problems and the changes that have taken place in the community today while chapter VI, the concluding chapter discusses on some observations and implications that can be made from my findings.